Investigation of wear resistance of drill bits with WC, Diamond-DLC, and TiAlSi coatings with respect to mechanical properties of rock. (February 2020) - Piri, Mostafa; Hashemolhosseini, Hamid; Mikaeil, Reza; Ataei, Mohammad; Baghbanan, Alireza
Abstract: Drilling is an important engineering operation with extensive application in many fields of industry including mining engineering, oil and gas exploration and exploitation, civil engineering, groundwater management, etc. Drill bits must be able to endure enormous stresses that gradually wear them down during the drilling operation. In rock drilling, wear resistance is a key determinant of the drill bit lifetime and hence the drilling cost, thus basically affecting the choice of drilling method for any given rock type. With the advent of new wear-resistant materials, they can be used to improve the resistance of drill bits against wear and erosion. This study investigated the wear resistance of drill bits with tungsten carbide (WC) coating, DLC-Diamond coating, and titanium-silica‑aluminum (TiAlSi) coating when drilling in three types of hard rock, namely Khoshtinat Granite (A1 ), White Natanz Granite (A2 ) and Nehbandan Granite (A3 ). The drilling tests were performed on cuboid specimens using a drilling machine at rotation speeds of 850, 900 and 950 rpm and penetration rates of 12, 18 and 24 mm/min. The results showed that for any fixed drilling conditions, the wear rates of the TiAlSi drill bit in A1, A2, and A3 were respectively 48%, 52%, and 60% lower than those of the WC drill bit. In the same rocks, the Diamond-DLC drill bit also showed 42%, 44.25%, and 55% lower wear rates than the WC drill bit. in addition to the observed changes in wear rate of the drill bits, the surface roughness created by these drills represents the optimum performance of the TiAlSi drill bit. It was observed that, as the mechanical properties of the rock (uniaxial compressive strength, Mohs hardness, Schimazek's abrasivity index and Young's Modulus) increased, the tested drill bits showed wider differences in terms of wear resistance. As the TiAlSi drill bit had the lowest wear rate (27%) and after that, the Diamond-DLC drill bit showed a better wear (30%) performance than the WC drill bit (60%). Highlights: Making a laboratory-scale device with the ability to change the parameters of operation for drilling tests. Coating the drill-bit with three layers. The effect of coating type on wear rate. The relationship between the mechanical parameters of the rock and the rate of wear of the drill bits.